College Students' Perspective Towards Lecturers' Work Ethics - Crizjale V Ahmad (Indonesian Journal of Educational Research and Technology, 2021)
The main objective of this study is to determine the college students' perspective on their teachers' work ethics. The researcher conducted this study at Notre Dame of Tacurong College towards 262 college students across all year levels and courses who were enrolled during the first semester of the academic year 2016-2017 as the respondents. The researcher uses convenient sampling to identify the individual respondents from each class and a researcher-made questionnaire to gather data for this study. The researcher uses different statistical tools such as frequency, percentage, mean, standard deviation, and ranking to treat the data. Findings reveal that out of 262 respondents, most are female second-year students enrolled in Bachelor of Science in Business Administration. Results show further that college students' perspective on teachers' work ethics generally practices to a great extent are lecturers use technology when teaching; lecturers dress appropriately in school; lecturers abide by the school policies, and lecturers show positive relationship towards school administration. Also, lecturers manage students' misbehaviour with patience.